Deployment of Artificial Intelligence for Implementation of Public administration Programme in Nigerian Universities - Sani Kasimu; Ibrahim Idris; Shafiu Yahya (MultiTech Publisher, 2024)
This paper assessed the effectiveness of artificial intelligence in the implementation of public administration programme in the universities. Secondary data were used in the paper. The data were collected from print and online publications. The paper established that deployment of artificial in the universities has aided effective implementation of public administration programme in the universities. Specifically, the study maintained that artificial intelligence has aided effective implementation of teaching, research, community services and academic services in the universities in Nigeria. Based on this, the paper recommends that universities administrators should sustain the full deployment of artificial intelligences in the universities administration and in the implementation of academic programme. Universities administrators should ensure more investment in the infrastructure facilities of artificial intelligence in all the universities across the country.